Antibacterial effect and evaluation of the inhibitory effect against efflux pump in Staphylococcus aureus by abietic acid: In vitro and in silico assays. (November 2022) - de Lima Silva, Maria Gabriely; da Silva, Lucas Yure Santos; de Freitas, Thiago Sampaio; Rocha, Janaina Esmeraldo; Pereira, Raimundo Luiz Silva; Tintino, Saulo Relison; de Oliveira, Maria Rayane Correia; Bezerra Martins, Anita Oliveira Brito Pereira; Lima, Maria Carolina Pacheco; Alverni da Hora, Gabriel Costa; Ramalho, Cicero L.G.; Coutinho, Henrique Douglas Melo; et al.
Abstract: Abietic acid is a diterpene found in resins mainly from diverse species of genus Pinus. The present study evaluated the antibacterial and inhibitory effect against the NorA and MepA efflux pump of Staphylococcus aureus by abietic acid using in vitro and in silico assays. The microdilution bacterial assay was used to evaluate antibacterial activity in standard bacteria (SA 25923 and EC 25922) and clinical isolates bacteria multiresistant (SA-10 and EC-06). Their association with antibiotics ampicillin, gentamicin, and ciprofloxacin was also estimated. Staphylococcus aureus (SA-1199B and SA-K2068) was used with a NorA and MepA pump machine, respectively, to verify the inhibitory effect using MIC methodology proposed by CLSI and Ethidium Bromide, an indicator of an efflux pump. Molecular dynamics and molecular docking calculations were used to evaluate and validate the interaction of abietic acid with NorA and MepA efflux pumps. The results demonstrated a significate reduction of MIC values to EC 25922 and SA 10 and showed a synergistic effect when combined with increased gentamicin susceptibility against multiresistant strains. The abietic acid showed direct activity against Staphylococcus aureus overexpressing gene of efflux pump, demonstrating the possibility of interference in the efflux pump NorA (SA 1199B) and MepA (SA K2068) mediated by hydrogen bonds and hydrophobic interactions. Together, these findings are promisors validating the potential antimicrobial activity and the possibility of using abietic acid as antibiotic adjuvant resistance breakers (ARBs) to treat infections caused by multiresistant bacteria. However, other studies are necessary to confirm this potential using the in vivo model. Graphical Abstract: ga1 Highlights: The abietic acid demonstrated inhibitory effect against EP by in silico assays. The abietic acid had synergic effects with different antibiotics. The abietic acid is a potential break antibiotic resistance (BRA) compound class.